Drug resistance profile of Mycobacterium tuberculosis in China: update until 2024 - Xu, Yannan; Liu, Sixuan; Zheng, Jiaxiong; Lin, Jianxiong; Gi, Liwei; Chang, Qiaocheng (Frontiers in Microbiology, 2025)
BackgroundThe situation of drug-resistant tuberculosis in China remains serious and complex. The majority of the study data are still derived from the 2,207 national survey of drug-resistant tuberculosis. In this study, we aimed to comprehensively characterize the prevalence of Mycobacterium tuberculosis (MTB) in China and update the catalogue of drug-resistant mutations while accounting for geographic variability.Materials and methodsThis study analyzed Mycobacterium tuberculosis (M. tuberculosis) isolates collected from 27 provinces, municipalities, and autonomous regions across China. All strains were analyzed for resistance to isoniazid, rifampicin, streptomycin, ethambutol, pyrazinamide, and quinolones based on the results of phenotypic drug sensitivity tests. The spatial and temporal distribution characteristics of drug-resistant strains were assessed based on the geographic origin and collection time of the isolates. The association between mutations and drug resistance was evaluated using mutation rates, positive predictive values, chi-square or Fisher’s exact test p-values, and 95% confidence intervals.Results55,388 MTB strains collected from 2002 to 2024 were analyzed, among which 15,078 were drug-resistant, including 7,848 multidrug-resistant strains. The resistance rates for INH, RFP, SM, EMB, PZA, and QS were 27.67, 25.33, 11.55, 6.19, 8.63, and 20.63%, respectively. Regional distribution patterns revealed that the eastern and western regions had the highest number of strains, but relatively low resistance rates. There was a low inflection point in 2019 for the resistance rates of all drugs except INH, whose resistance rate continued to increase after 2017. A total of 754 non-synonymous mutations were identified, with the highest mutation rates observed in INH (32.91%), RIF (28.98%), and QS (14.47%). The dominant mutation sites were katG (315AGC → ACC), rpoB (531TCG → TTG), and gyrA (94GAC → GGC), respectively. In addition, 96 newly detected mutations potentially associated with drug resistance were identified, including ahpC (11CCG → CCG) and pncA (226ACT → CCT). Combined mutations were most frequently observed in rpoB + rpoB, katG + katG, and katG + inhA, with other double-mutation combinations also being predominant.ConclusionOur analysis demonstrates that drug-resistant tuberculosis remains a serious challenge in China. Newly identified resistance-conferring mutations should be prioritized and integrated with the specific epidemiological characteristics of DR-TB in China to support the development and implementation of rapid diagnostic technologies.